Application of the Tam Model on Instagram Ads - Panjaitan, Arop Ria Saulina; Rowena, Janny; Handra, Tessa (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
Indonesia fashion industry is rapidly growing, driven by high household consumption and widespread social media use. Instagram Ads, a popular tool for digital marketing, provides targeted advertising features. However, limited research explores user perceptions influencing its adoption, particularly in the fashion sector. This study investigates factors affecting the intention to use Instagram Ads by applying constructs from the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB), including perceived ease of use, perceived usefulness, trustworthiness, and attitudes toward Instagram Ads. A quantitative approach was used with Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from Instagram Ads users in the fashion industry, testing nine hypotheses to assess relationships between key variables. The results indicate that perceived ease of use positively influences perceived usefulness (H1), trustworthiness (H2), and attitudes toward Instagram Ads (H3). Perceived usefulness impacts trustworthiness (H4), attitudes (H5), and intention to use Instagram Ads (H6). While trustworthiness affects attitudes (H7), it does not directly influence intention to use Instagram Ads (H8). Attitudes significantly determine intention to use Instagram Ads (H9). This study extends previous research by highlighting the role of ease of use and perceived usefulness in shaping user attitudes and trust. The findings offer practical implications for businesses looking to optimize digital marketing strategies and theoretical contributions by integrating TAM and TPB in a social media advertising context.